The tensile evaluation of the Epoxy/Keratin short fibre as new composites / Ahmad Zafir Romli, Mohd Hanafiah Abidin and Hazizan Md Akil - Romli, Ahmad Zafir; Abidin, Mohd Hanafiah; Md Akil, Hazizan (Research Management Institute (RMI), 2009)
Production of bio-composites using biodegradable filler/fibre or matrix has been increasing steadily for the past decade. In the case of fibre reinforced polymer composites, natural fibres such as jute, hemp and kenaf have been widely reported. Apart from cellulosic based natural fibre, there are other potential fillers from animal based by-products such as keratin from chicken feathers. In this study, an epoxy/keratin composite has been produced using a pressure assisted hand lay-up technique to form flat homogenized board. The percentage feather content by weight was varied accordingly (i.e. 10, 20, 30, 40 and 50 %). The board underwent standard tensile strength testing at 5mm.min-1 and elucidated that the ultimate tensile strength and strain decreases as the feather composition percentage increases. The Young's modulus indicated little effect with increasing feather composition percentage. A fractured piece of sample produced from the tensile testing was evaluated with respect to fracture behaviour using scanning electron microscopy (SEM). The tensile testing indicates that the composite with the maximum feather composition percentage (50 %) has the potential to be used in non-structural applications.